NEW APPROACHES IN EDUCATION - Boltayeva R.A (Bright Mind Publishing, 2025)
As in every field, working with the reforms taking place in education requires studying the existing problems and trying to find solutions. From a pedagogical point of view, scientific approaches are also envisaged to be implemented within the framework of their work.
Keywords: scientific approach, pedagogical view, individual approach, pedagogical technology, pedagogical skills.